PERAN PETUGAS LAPAS TERHADAP PENCEGAHAN IMS DAN HIV/AIDS PADA NARAPIDANA - Zulkarnain, Elfian; Istiaji, Erdi; Agustin, Ulviyah Rizqi (FKM - UNEJ, 2011)
The study aimed to describe the role of prison officers to the prevention of STIs and HIV/AIDS in the Correctional Institution inmates Class II-A Jember conducted a qualitative approach using snowball technique. Indepth interviews was done in six prison officers to obtain a more indepth information about the variables studied. These variables include the characteristics, knowledge, attitudes and the role that prison officers against STIs and HIV / AIDS on prisoners. Results showed that at the last general prison officer education is a high educational level (graduate degree) and secondary education level (high school graduate or equivalent) with a length of work <15 years. Average prison officer knowledge about STIs and HIV / AIDS are at moderate and high categories, with the attitude of support. In general, prison officers have a good role in the prevention of STDs and HIV / AIDS, but in certain respects is still room for improvement. Keywords: Prison officer, Prisoner, Sexually Transmitted Infections (STIs), HIV / AIDS